Respuesta :
Answer is 2a.
(1) Rephrase the expression as (15-13)a
(2) Solve the parenthesis and get 2
(3) Multiply 2 by a = 2a
(1) Rephrase the expression as (15-13)a
(2) Solve the parenthesis and get 2
(3) Multiply 2 by a = 2a
Answer:
(15-13)a=2a
Step-by-step explanation:
When you want to factor an expression you have to take out the number or variable that everything is multiplied by. In this case: 15a - 13a, both 15 and 13 are being multiplied by the variable a, so we can take out that number and write it only once and multiplied by the two numbers:
(15-13)a,
we know that in math 15a - 13a = (15-13)a, now we can add or subtract the numbers and the answer will be: 15-13=2, so (15-13)a = 2a.